2018
DOI: 10.1002/bdm.2069
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Fast and Frugal Heuristics with a Model of Memory‐based Cue Generation

Abstract: Although the fast and frugal heuristics have been studied extensively, relatively little attention has been paid to how cues are generated to be used within the heuristics. The goal of this paper is to propose and test a memory-based model of how cues are generated and used in cue-based inferences. The current study advances theory by integrating the fast and frugal heuristics with HyGene, a memory-based model of how decision makers generate and evaluate hypotheses. Using archival data in which memory retrieva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 57 publications
(88 reference statements)
1
6
0
Order By: Relevance
“…By using a multi-method approach, we found that the availability of information held in memory had a two-fold effect on decision making, namely the cued option's increased weight and an increase in more compensatory information search behavior. This result corresponds with a growing number of studies, which emphasize the role of memory during judgment and decision making (Lawrence et al, 2018;Platzer et al, 2014;Renkewitz & Jahn, 2012) and therefore it is highly relevant to both cognitive and applied researchers who are interested in understanding judgment and decision making processes. It is especially relevant to marketers who aim to presenting products to their customers in a manner that optimizes their profit.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…By using a multi-method approach, we found that the availability of information held in memory had a two-fold effect on decision making, namely the cued option's increased weight and an increase in more compensatory information search behavior. This result corresponds with a growing number of studies, which emphasize the role of memory during judgment and decision making (Lawrence et al, 2018;Platzer et al, 2014;Renkewitz & Jahn, 2012) and therefore it is highly relevant to both cognitive and applied researchers who are interested in understanding judgment and decision making processes. It is especially relevant to marketers who aim to presenting products to their customers in a manner that optimizes their profit.…”
Section: Discussionsupporting
confidence: 63%
“…Recent research has proposed that the availability of information in memory is an important source of influence on judgment and decision making (Lawrence et al, 2018;Platzer et al, 2014). This study builds on these results and extends them to preferential choice tasks, which are frequently studied in consumer research.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Recent research also showed that the availability of attribute information in memory influences information search, which can also alter subsequent choice behavior (Lawrence, Thomas, & Dougherty, 2018;Platzer, Bröder, & Heck, 2014). Consequently, despite the car dealer's intention to increase the weight of only one specific attribute in the opening scenario, changing the availability of one attribute can change the weight of the remaining attributes as well.…”
Section: Introductionmentioning
confidence: 99%